MOROCCAN MINI-FICTION MODEL IN AR-RIHANI'S 'HA’AL-HURRIYAH' ANTHOLOGY (MODEL FIKSI MINI MAROKO DALAM ANTOLOGI 'HA’AL-HURRIYAH' KARYA AR-RIHANI) - Drei Herba Ta'abudi (UIN Raden Mas Said Surakarta, 2018)
The aim of this research was to describe the short-short story (al-qisah al-qasirah jidan) of Morocco in Ha’al-Hurriyah anthology by Muhammad Said ar-Rihani by using structural approach. This approach is selected to show the text objectively. This paper analyzed the short short story using the theory of Rimmon-Kenan naratology and Qalyubi stylistics. It tried to find out how the storytelling models in the short-short stories entitled Haitsuma Kana al-Zulmu Fatsamati Watani and Ghidza’ al-A’mal in the anthology are and how language style are used in both short-short stories. The results of this research show that for storytelling, both short-short stories uses narrative and dialogue technique, each of which lead to the centralization and compaction of the theory. Both short-short stories contain structural aspects of metaphorical repetitions whereas in the imaginary realm, there are characteristics of title selection, the use of majaz (metaphor) and itnab (hyperbole).